Moisture induced weathering of volcanic tuffstone. (30th October 2018) - Lubelli, Barbara; Nijland, Timo G.; Tolboom, Hendrik-Jan
Graphical abstract: Highlights: The response of Weibern and Ettringen tuff stones to moisture has been investigated. A purpose-made weathering test was carried out to simulate the wetting-drying process. Pore size, porosity, moisture transport and hygric behaviour of both stones were measured. Both tuff stones have an extreme dilation in response to RH changes and to wetting. All results show that moisture gradients in tuff elements may enhance decay in this stone. Abstract: Tuffstone elements with a large length/width ratio often suffer damage in the form of cracks parallel to the surface and spalling of the outer layer. This study aimed at verifying if this damage may be the result of a differential dilation between parts with different moisture content. The research, carried out on Ettringen and Weibern tuff, comprised a weathering test and measurements of porosity, moisture transport and hygric behaviour of the stones, supplemented by environmental X-ray diffraction analyses. Results support the hypothesis that moisture gradients in tuff elements may enhance decay in this stone.